2021
DOI: 10.1002/hbm.25640
|View full text |Cite
|
Sign up to set email alerts
|

Somatic engagement alters subsequent neurobehavioral correlates of affective mentalizing

Abstract: Socio-emotional encounters involve a resonance of others' affective states, known as affect sharing (AS); and attribution of mental states to others, known as theory-ofmind (ToM). Empathy necessitates the integration of both processes, yet their interaction during emotional episodes and subsequent generation of inferences on others' affective states has rarely been tested. To address this, we developed a novel experimental design, wherein we manipulated AS by presenting nonverbal emotionally negative movies tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
(136 reference statements)
0
2
0
Order By: Relevance
“… 36 Evidence from anxiety-like behaviors in mouse models of chronic pain highlighted the crucial role of nNOS-expressing neurons in the ventromedial prefrontal cortex (vmPFC) in the manifestation of pain-induced anxiety 19 ; furthermore, these neural alterations were not confined solely to anxiety (eg, pathological or physiological stress-related responses). 12 , 32 Taken together, neuroplasticity plays a significant role in the development and manifestation of chronic pain and negative emotions, likely involving similar brain structures, neurotransmitters, and pathways. Having said this, an alternative explanation also exists—it has also been shown by recent studies that the altered FCs between patients with chronic pain and HC were associated with the timing of assessment, specifically the presence or absence of pain at that moment of MR scanning.…”
Section: Discussionmentioning
confidence: 99%
“… 36 Evidence from anxiety-like behaviors in mouse models of chronic pain highlighted the crucial role of nNOS-expressing neurons in the ventromedial prefrontal cortex (vmPFC) in the manifestation of pain-induced anxiety 19 ; furthermore, these neural alterations were not confined solely to anxiety (eg, pathological or physiological stress-related responses). 12 , 32 Taken together, neuroplasticity plays a significant role in the development and manifestation of chronic pain and negative emotions, likely involving similar brain structures, neurotransmitters, and pathways. Having said this, an alternative explanation also exists—it has also been shown by recent studies that the altered FCs between patients with chronic pain and HC were associated with the timing of assessment, specifically the presence or absence of pain at that moment of MR scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, social engagement, together with emotional and cognitive engagement, plays a crucial role when tasks deal with the problems and contexts of complex social relationships, when students are directed to work with others, and when value systems conflict [24,35], especially during study abroad [36]. As argued by Shany et al [37], socioemotional encounters involve a resonance of others' affective states and attribution of mental states to others where empathy can integrate both states. Moreover, emotional aspects of the experience gained from tasks or other work assignments can be used for visualizing and, consequently, trigger somatic engagement with learning [37].…”
Section: Learning Dynamics In Technology-enhanced Education Ecosystemsmentioning
confidence: 99%
“…As argued by Shany et al [37], socioemotional encounters involve a resonance of others' affective states and attribution of mental states to others where empathy can integrate both states. Moreover, emotional aspects of the experience gained from tasks or other work assignments can be used for visualizing and, consequently, trigger somatic engagement with learning [37].…”
Section: Learning Dynamics In Technology-enhanced Education Ecosystemsmentioning
confidence: 99%
“…The authors further support this distinction by citing empirical evidence from research in personality, developmental disorders, and neurological studies, supporting the notion that cognitive and affective empathy are separate constructs. Specifically during film watching, Shany et al ( 2021 ) found different neural patterns for affect sharing, affective ToM, and cognitive ToM. To capture these dissociative components in the processing of dramatic irony scenes, we considered cognitive and affective mental states both separately and together in our analysis.…”
Section: Introductionmentioning
confidence: 99%